Potency of Solid Lipid Nanoparticle (SLN)-Modified Luteolin-based Polyethylene Glycol (PEG) on Allium fistulosum as Innovation Therapy of Malaria Falciparum - Martha Ariesaka, Kiky; Taufiqurrahman, Mudzakkir; Mirza Nuryady, Moh (KnE Life Sciences, 2021)
In 2013, 198 million cases of malaria were reported globally and 584,000 of them died. As much as 78% of cases occurred in children under five years of age. Indonesia is a has the second highest malaria incidence rate after India in the Asian region. Severe malaria can be characterized by the presence of severe anaemia, hyperparasitemia or cerebral malaria. Severe anaemia due to malaria or severe malaria anaemia (SMA) often occurs in children who suffer from falciparum malaria. SMA occurs due to a decrease in COX-2-PGE2, caused by phagocytosis of PfHz (Plasmodium falciparumderived Hemozoin) by monocytes, macrophages and neutrophils. PfHz is a crystalline compound formed from the aggregation of heme hosts. Fe2+ is one of the constituents of heme, luteolin can bind Fe2+ so that the bond between luteolin and Fe2+ in heme prevents the formation of PfHz, so that severe anaemia can be prevented. Like other naturally occurring active compounds, luteolin has low bioavailability in the body so it is encapsulated using Solid Lipid Nanoparticles (SLN) and Polyethylene Glycol (PEG). SLN is useful for increasing the bioavailability of luteolin in the body, while PEG is useful for preventing the destruction of luteolin-SLN by RES. The modified construction process includes the following steps: (1) luteolin extraction from Allium fistulosum and (2) luteolin encapsulation using SLN-PEG. The potential dose to be administered orally to humans is 2.43–8.11 µg/kg body weight. Keywords: luteolin, polyethylene glycol, severe malaria anaemia, solid lipid nanoparticles